SOME ISSUES OF INCREASING THE EFFICIENCY OF COOPERATION WITH PARENTS IN THE ORGANIZATION OF PRESCHOOL EDUCATION (IN THE EXAMPLE OF DMTT NUMBER 14 IN CHUST DISTRICT) - Urinboyeva Nodirabegim (Social science and innovation, 2023)
The article examines various aspects of increasing the effectiveness of interaction with parents in a preschool education organization on the example of state preschool education organization No. 14 in Cusht district. The work carried out in the preschool education system in close cooperation with parents and their effect on positive achievements in children’s education are also analyzed in detail in the article